2019
DOI: 10.3897/subtbiol.31.36241
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Oribatida (Acari) along a depth gradient in forested scree slopes

Abstract: Mesovoid shallow substratum (MSS) of scree slopes constitutes a transition habitat between the soil and the network of voids in the vadose zone of a bedrock massif. In the present study, the vertical distribution of oribatid communities along a depth of 95 cm was studied at five forested MSS sites in the Western Carpathians, Slovakia. The sites differed in type of bedrock, topography and gradient of the microclimate and nutrients content. In all, 909 specimens were captured in subterranean traps exposed for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Some researchers (Marian et al, 2018;Bluhm et al, 2019) showed that the species richness of oribatid mites does not depend on the litter belonging to a particular tree species. Both species richness and activity of oribatid correlates with the organic carbon content in the soil substrate (Jakšová et al, 2019). Our study clearly manifested these regularities.…”
Section: Discussionsupporting
confidence: 72%
“…Some researchers (Marian et al, 2018;Bluhm et al, 2019) showed that the species richness of oribatid mites does not depend on the litter belonging to a particular tree species. Both species richness and activity of oribatid correlates with the organic carbon content in the soil substrate (Jakšová et al, 2019). Our study clearly manifested these regularities.…”
Section: Discussionsupporting
confidence: 72%
“…Improving our understanding of the biodiversity gradients and their drivers is still an important requirement to deal with impending species loss. Therefore, many studies have explored environmental gradients as explanatory variables for biodiversity patterns along different geographic scales (Rahbek, 2004 ; Whittaker et al., 2007 ) such as (a) latitude (Stehli et al., 1969 ; Rohde, 1992 ; Pontarp et al., 2019 ; Etienne et al, 2019 ), (b) elevation (Colwell & Rangel, 2010 ; Graham et al., 2014 ; Hutchinson, 1953 ; Lomolino, 2001 ; Nogués‐Bravo et al., 2008 ; Rahbek, 1995 ; Rahbek et al., 2019 ; Sanders & Rahbek, 2012 ), (c) tree height in forests (Petter et al., 2016 ), (d) depth in soils (Jakšová et al., 2019 ; Rendoš et al., 2016 ), or (e) depth in water (Gong et al., 2015 ; Rex & Etter, 1998 ; Smith & Brown, 2002 ). These geographic gradients share some environmental gradients, which are expected to influence spatial structuring of diversity gradients, for example, temperature, light, or seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…The application of this method requires: 1) deciding whether the formation of the scree slope is natural or anthropogenic, as this criteria can be biased; 2) selecting appropriate rock types within the lithology of the study site, as long as they allow the formation of scree slopes (this includes non-karst areas) and 3) taking into account vegetation coverage of the area, which can mask scree slopes in the in situ verification stage (Rendoš et al 2014;Rudy et al 2018;Jakšová et al 2019). One method to overcome this last complication is to add an updated vegetation layer to the mapping step, when available, in order to better predict these events.…”
Section: Discussionmentioning
confidence: 99%